2000
DOI: 10.1001/jama.284.8.1001
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Rabies Postexposure Prophylaxis Treatment for Animal Exposures

Abstract: These results suggest that use of RPEP is often inappropriate. Greater compliance with current guidelines would increase RPEP use. Physician education, improved coordination with public health officials, and clarification of RPEP guidelines could optimize use of this expensive resource. JAMA. 2000;284:1001-1007

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
7

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(67 citation statements)
references
References 14 publications
2
58
0
7
Order By: Relevance
“…In rural Pennsylvania, cat encounters accounted for 44 % of human PEPs, more than any other species [26]. In urban emergency rooms, cats accounted for >15 % of patients receiving PEP [42]. The average rabid cat generates between 1 and 6 human PEPs [19,24].…”
Section: Discussionmentioning
confidence: 99%
“…In rural Pennsylvania, cat encounters accounted for 44 % of human PEPs, more than any other species [26]. In urban emergency rooms, cats accounted for >15 % of patients receiving PEP [42]. The average rabid cat generates between 1 and 6 human PEPs [19,24].…”
Section: Discussionmentioning
confidence: 99%
“…et al suggest that the use of PEP was inappropriate in 40% of vaccinated patients. 17 In our study, PEP was given to a majority of patients with dog or cat exposures, and these animals accounted for 70% of all vaccinated cases. Since domestic animals can serve as a link for rabies virus between wildlife and humans, vaccination of dogs and cats continues to be an extremely effective public health measure in preventing rabies in humans.…”
Section: Discussionmentioning
confidence: 77%
“…A review of the appropriateness of rabies PEP based on data from 11 university-affiliated emergency departments determined that rabies PEP was inappropriately administered to 40 percent of the patients who received PEP. 17 Likewise, a study conducted in Florida found that rabies PEP was unnecessarily given to almost one quarter of the 160 patients who received rabies PEP in 1997 and 1998. 18 Increased involvement of public health staff in the decision-making process through increased reporting of animal exposures and rabies PEP cases may reduce the number of people who receive rabies PEP needlessly and help assure that it is given when indicated.…”
Section: • Discussionmentioning
confidence: 99%